Hubungan Ketangguhan Mental dengan Prokrastinasi Akademik Pada Mahasiswa Aktif Berorganisasi - Rizqan Fadhilah; Irin Riamanda; Mirza Mirza; Arum Sulistyani (Syiah Kuala Psychology Journal, 2025)
Students must be able to harmonize academic and non-academic processes, one of which is organizational activities. It is not uncommon for some students to experience the inability to coordinate academic obligations with active organizational activities, causing the adverse effects of academic procrastination. Therefore, students are expected to be able to foster mental toughness to maintain performance in conditions and circumstances. The study was conducted with the aim of knowing the relationship between mental toughness and academic procrastination in active organizational students. Using a correlational quantitative method using accidental sampling method and as many as 327 active organizational students of class 2020-2022 Syiah Kuala University became research samples by filling out the mental toughness questionnaire 18 (MTQ-18) and Tuckman Procrastination Scale (TPS) research instruments. The study showed a significant value (p) = 0.001 with a correlation coefficient of (r) = - 0.242 which means there is a negative relationship between mental toughness and academic procrastination, the lower the mental toughness, the higher the procrastination and vice versa the higher the mental toughness, the lower the academic procrastination. This study also provides implications in the form of suggestions that students can do to be able to balance college goals with organizational activities, one of which is by increasing enthusiasm for learning to reduce pressure and anxiety during the academic process so that it can also increase mental toughness in themselvesMahasiswa harus dapat menyelaraskan proses akademik maupun non-akademik salah satunya kegiatan organisasi. Tidak jarang bagi beberapa mahasiswa mengalami ketidakmampuan mengoordinasikan kewajiban akademik dengan kegiatan aktif organisasi sehingga menimbulkan dampak buruk prokrastinasi akademik. Oleh karena itu, mahasiswa diharapkan mampu menumbuhkan ketangguhan mental untuk mempertahankan kinerja dalam kondisi dan keadaan. Penelitian dilakukan dengan tujuan untuk mengetahui adanya hubungan ketangguhan mental dengan prokrastinasi akademik pada mahasiswa aktif berorganisasi. Menggunakan metode kuantitatif korelasional dengan menggunakan metode sampling accidental dan sebanyak 327 mahasiswa aktif berorganisasi angkatan 2020-2022 Universitas Syiah Kuala menjadi sampel penelitian dengan mengisi instrumen penelitian Mental Toughness Questionnaire 18 dan Tuckman Procrastination Scale. Penelitian menunjukkan nilai signifikansi (p)=0.001 dengan koefisien korelasi sebesar (r)=-0.242 yang berarti terdapat hubungan negatif antara ketangguhan mental dengan prokrastinasi akademik, semakin rendah ketangguhan mental maka semakin tinggi prokrastinasi dan sebaliknya semakin tinggi ketangguhan mental maka semakin rendah prokrastinasi akademik. Penelitian ini juga memberikan implikasi berupa saran yang dapat dilakukan mahasiswa agar mampu menyeimbangkan tujuan berkuliah dengan kegiatan organisasi salah satunya dengan meningkatkan antusiasme belajar agar mengurangi tekanan dan kecemasan selama proses akademik berlangsung sehingga juga dapat meningkatkan ketangguhan mental pada diri sendiri.